Explaining racial disparities in surgical survival: a tapered match analysis of patient and hospital factors - Lasater, Karen B; Rosenbaum, Paul R; Aiken, Linda H; Brooks-Carthon, J Margo; Kelz, Rachel R; Reiter, Joseph G; Silber, Jeffrey H; McHugh, Matthew D (BMJ open, 2023)
ObjectivesEvaluate whether hospital factors, including nurse resources, explain racial differences in Medicare black and white patient surgical outcomes and whether disparities changed over time.DesignRetrospective tapered-match.Setting571 hospitals at two time points (Early Era 2003–2005; Recent Era 2013–2015).Participants6752 black patients and three sets of 6752 white controls selected from 107 001 potential controls (Early Era). 4964 black patients and three sets of 4964 white controls selected from 74 108 potential controls (Recent Era).InterventionsBlack patients were matched to white controls on demographics (age, sex, state and year of procedure), procedure (demographics variables plus 136 International Classification of Diseases (ICD)-9 principal procedure codes) and presentation (demographics and procedure variables plus 34 comorbidities, a mortality risk score, a propensity score for being black, emergency admission, transfer status, predicted procedure time).Outcomes30-day and 1-year mortality.ResultsBefore matching, black patients had more comorbidities, higher risk of mortality despite being younger and underwent procedures at different percentages than white patients. Whites in the demographics match had lower mortality at 30 days (5.6% vs 6.7% Early Era; 5.4% vs 5.7% Recent Era) and 1-year (15.5% vs 21.5% Early Era; 12.3% vs 15.9% Recent Era). Black–white 1-year mortality differences were equivalent after matching patients with respect to presentation, procedure and demographic factors. Black–white 30-day mortality differences were equivalent after matching on procedure and demographic factors. Racial disparities in outcomes remained unchanged between the two time periods spanning 10 years. All patients in hospitals with better nurse resources had lower odds of 30-day (OR 0.60, 95% CI 0.46 to 0.78, p<0.010) and 1-year mortality (OR 0.77, 95% CI 0.65 to 0.92, p<0.010) even after accounting for other hospital factors.ConclusionsSurvival disparities among black and white patients are largely explained by differences in demographic, procedure and presentation factors. Better nurse resources (eg, staffing, work environment) were associated with lower mortality for all patients.